A K-bubble and nano-oxide composite reinforced W-based material and preparation method thereof
Through the ball milling and sintering process of Al-Y amorphous alloy and W-K powder, the dispersion distribution of nano-oxide particles and the formation of K bubbles in W-K alloy are achieved, solving the problems of coarse oxide particles and partially aggregated grain boundaries, and achieving the dual strengthening effect of high temperature and room temperature of W materials.
Patent Information
- Application Number
- CN202310532789.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-05-12
AI Technical Summary
The oxide particles in the existing W-K alloys are coarse and the grain boundary is partially aggregated, resulting in deterioration of material properties and it is difficult to achieve the combined dual strengthening effect of soft K bubbles and hard oxide particles.
Through the low melting point and strong chemical activity of the Al-Y amorphous alloy, the ball mill is ball-milled with W-K powder, and then mixed evenly, and then the first step of sintering is performed at a temperature slightly higher than the Al-Y amorphous melting point, introducing a liquid phase sintering effect, so that the Y and O components are fully diffused into the W grains, forming nano-oxide particles; then the second step of sintering is performed to form K bubbles.
The joint joint strengthening effect of hard oxide particles and soft K bubbles on W materials is achieved. The distribution state of K bubbles and nano Y2O3 particles in the material can be regulated through subsequent plastic processing, combining the advantages of high-temperature strengthening of W-K and room-temperature strengthening of ODS-W.
Smart Images

Figure CN116555653B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a W-based material compositely reinforced by K bubbles and nano-oxides, a preparation method and application thereof, and belongs to the technical field of powder preparation engineering. Background Art
[0002] Adding dispersed second-phase particles to W is an important method to increase the working temperature of W materials and improve their service performance. At present, the second-phase particles added to practical W materials mainly include K bubbles, oxides and carbides.
[0003] The K bubbles of WK alloy can effectively pin the grain boundaries in W materials, prevent the movement of grain boundaries, and obtain excellent high-temperature microstructure stability (recrystallization temperature exceeds 1700℃) and creep resistance. The excellent high-temperature performance of WK alloy has been widely used in engineering fields such as lighting. The main processes for industrial production of WK alloy include: 1. Preparation of AKS-W (aluminum potassium silicon doped tungsten) powder by wet chemical method; 2. Preparation of WK sintered blanks by high-temperature sintering; 3. Subsequent plastic processing such as rotary forging. After processing, K bubbles are distributed at the grain boundaries in a discontinuous streamline shape. Since K bubbles are soft phases, their strengthening effect on the W matrix is limited, and the room temperature strength of the material is low. The addition of hard second phases such as oxides has a significant effect on improving the room temperature strength of W materials. Studies have shown that by adding nano-scale Y2O3 and other strengthening particles to W (ODS-W alloy), the room temperature strength, hardness and thermal shock resistance of the material can be greatly improved, which is an important way to obtain high-strength W alloys. However, the addition of hard particles such as oxides has limited effect on increasing the recrystallization temperature of W materials (the recrystallization temperature is close to 1500℃), which makes it difficult to meet the growing demand for high-temperature service performance. The production process of ODS-W is similar to that of WK, and also includes three stages: powder making, sintering and subsequent deformation processing.
[0004] In view of the complementary advantages of WK and ODS-W alloys, people have recently tried to obtain high-strength W alloys with good high-temperature stability through the combined action of K bubbles and oxides. For example, Chen et al. prepared WKY composite powder by adding 0.05-0.5wt.% Y (weight percentage) to WK powder using mechanical alloying technology, and then prepared advanced W alloys by spark plasma sintering technology (SPS). Due to the strong chemical affinity between Y and O impurities in WK powder, WK alloys containing Y2O3 particles were obtained after sintering the composite powder with a Y content of more than 0.1wt.%, but Y2O3 was formed at the triangular grain boundaries and was in the micrometer range. Studies have shown that the introduction of Y has a certain fine-grain strengthening effect on the matrix W grains; however, when the addition amount of Y exceeds 0.1wt.%, micron-sized Y2O3 particles will form and aggregate at the grain boundaries. Because the size of this oxide is too large (non-nanoscale) and agglomerated at the grain boundaries, this not only fails to induce the second phase dispersion strengthening effect, but also causes the mechanical properties of the material to deteriorate significantly (Inter.J.Refra.Metals and Hard Mater.103(2022)105739).
[0005] In order to overcome the shortcomings of coarse oxide particles and grain boundary segregation in WK alloys prepared by prior art, this patent proposes a W material and its preparation method in which the grain boundary is mainly strengthened by K bubbles and the grain is dispersed and strengthened by nano-oxide particles. Specifically, it is intended to utilize the low melting point, strong chemical activity and strong capillary diffusion ability of the amorphous liquid phase of Al-Y amorphous alloy, and ball mill it with WK powder. After mixing evenly, the first step of sintering is carried out at a temperature slightly higher than the melting point of Al-Y amorphous. The liquid phase sintering effect is introduced by amorphous melting, so that the Y and O components are fully diffused into the interior of the W grains, and the oxides are formed by in-situ reaction to overcome the problem of oxide grain boundary agglomeration generated during the sintering of WKY powder; then the temperature is raised and the second step of sintering is carried out using the conventional WK alloy sintering process, so that residual impurities such as Al and Si are volatilized normally, and the remaining K element forms K bubbles. Through the above two-step sintering process, a W material with nano-Y2O3 particles dispersed in the crystal and K bubbles at the grain boundary is obtained. The size and distribution of K bubbles can be further controlled by subsequent plastic processing to achieve the ideal composite strengthening effect of K bubbles and oxides on W materials. This soft / hard phase composite strengthened W material realized by K bubbles and nano-oxides combines the advantages of high temperature strengthening of WK and room temperature strengthening of ODS-W. It provides the possibility of preparing high-strength W alloys with good high temperature stability, and is conducive to expanding the applicability of W materials in high temperature environments, and has good development prospects. Summary of the invention
[0006] The purpose of the present invention is to provide a soft / hard phase composite strengthened W material with grain boundaries strengthened mainly by K bubbles and nano-oxide particles dispersed in the grains and a preparation method thereof. The purpose is to solve the problems existing in the existing WK alloys containing oxides: (1) the dual strengthening effect of soft K bubbles and hard oxide particles is not truly achieved; (2) the oxides are only formed at the grain boundaries, and the particle size cannot reach the nanometer level, and the dispersion strengthening effect cannot be achieved; 3) when the Y addition exceeds 0.1wt.%, the Y2O3 micron particles will precipitate and segregate at the grain boundaries, resulting in the deterioration of material properties.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A W-based material reinforced by K bubbles and nano-oxides has the following organizational characteristics: W polycrystals with a size of 2 to 10 μm are used as the matrix; the nominal content of K in the material is 30 to 90 ppm, appearing at the grain boundaries in the form of K bubbles with a size of about 0.1 to 1 μm, and the final size and distribution state of these K bubbles can be further regulated by subsequent plastic processing; Y2O3 nanoparticles are dispersed and evenly distributed on the W matrix, and the size (5 to 50 nm) and number density of the Y2O3 nanoparticles can be regulated by a sintering process, and the volume fraction corresponding to the number density is between 0.5% and 5% (when the particle size is constant, it corresponds to the volume fraction occupied by oxide particles, and the volume fraction can be regulated by the sintering raw material ratio and the sintering process).
[0009] A method for preparing a W-based material reinforced by K-bubble and nano-oxide composite, firstly preparing Al with a melting point below 1100°C by arc melting combined with melt atomization technology 100-a Y a (55≤a≤75, atomic percentage) amorphous powder; then, the amorphous powder was sieved and mixed with commercially available AKS-W powder as raw materials, and the ingredients were prepared based on the nominal composition of the target W alloy sintered body. After mixing, the mixture was placed in anhydrous ethanol medium environment for high-energy ball milling to obtain Al 100-a Y a The amorphous and AKS-W composite powder is taken out and dried; finally, a W material with dispersed Y2O3 nanoparticles on the matrix and K bubbles formed at the grain boundaries is prepared by hot pressing sintering technology.
[0010] The specific steps are as follows:
[0011] (1) The first step is to prepare Al 100-a Y a Powder material
[0012] First, industrial pure metal is used as raw material, and the atomic percentage composition is Al 100-a Y a(55≤a≤75) alloy, place it in a water-cooled copper crucible in a non-consumable arc melting furnace and evacuate to ≤3×10 -2 Pa, and fill with 0.01-0.02MPa industrial pure Ar gas for non-consumable arc melting, the working current of melting is 120-150A; turn the alloy upside down and melt it repeatedly for 3 times to obtain Al with uniform composition 100-a Y a Alloy ingot.
[0013] Al 100-a Y a The alloy ingot is crushed and placed in a graphite crucible for atomization and powder making: medium frequency induction heating is used to heat the alloy to a certain temperature (slightly higher than Al 100-a Y a The melting point of the alloy) is kept warm for 2 to 5 minutes. It is sprayed out and cooled using atomization technology (the spray pressure of the atomization gas is 2 to 5 MPa, and the aperture of the guide rod nozzle is 1 mm) to obtain a spherical powder material with a particle size between 5 and 30 μm, which is sieved and set aside. The amorphous structure of the powder is confirmed by X-ray diffraction (XRD).
[0014] (2) The second step is to prepare Al 100-a Y a +AKS-W composite powder
[0015] Commercially available AKS-W powder was used as the matrix material, and Al 100-a Y a Amorphous powder is used as an additive, weighed, configured, and composite powder. The general formula of the composite powder is AKS-W+0.6~4.0wt.%Al 100-a Y a (The corresponding nominal composition of the target alloy is WK-0.3-3.0wt.%Y, where Y mainly exists together with O in the form of Y2O3). After mixing, it is put into a ball mill together with grinding balls (material-ball ratio is 1:5-1:10), and high-energy ball milling is performed in anhydrous ethanol medium environment, the ball mill speed is 150-200rpm, and the ball milling time is 10-30h. Finally, the ball-milled powder is taken out, dried in a vacuum drying oven and set aside.
[0016] (3) The third step is to prepare WK-Y2O3 sintered body by vacuum hot pressing
[0017] The composite powder (target alloy raw material) obtained in step 2 is placed in a vacuum hot pressing sintering furnace for sintering to obtain the target alloy sintered body. The sintering preload pressure is 30 MPa and the vacuum degree is 1×10 -2Pa, mainly including two stages: the first stage sintering temperature is 1100-1200℃, sintering pressure is 70MPa, and holding time is 60min; the second stage sintering temperature is 1700-1850℃, sintering pressure is 70MPa, and holding time is 60-120min. Then the furnace is cooled to room temperature, the sintered body sample is taken out, and the density and morphology of the sintered body are observed.
[0018] Application of a W-based material reinforced by K bubbles and nano-oxides: The W-based material can be further regulated in size and distribution of K bubbles through subsequent plastic processing (refer to conventional WK alloy plastic processing methods) to achieve the best soft / hard phase coupling dispersion strengthening effect. This provides a simple and effective way for the future powder metallurgy to develop new W alloy materials with excellent high temperature performance and high strength.
[0019] The beneficial effects of the present invention are:
[0020] (1) Using Al 100-a Y a The special effect of amorphous is that in a hydrogen-free environment, through vacuum hot pressing sintering technology, nano-scale oxide strengthening phase is dispersed in situ on the WK alloy matrix (including inside the W grains), truly realizing the joint strengthening effect of hard oxide particles and soft K bubbles on W materials;
[0021] (2) The size and number density of Y2O3 oxide nanoparticles can be determined by Al 100-a Y a The amount of amorphous powder added and the sintering process can be controlled; the final shape and distribution of K bubbles in the material can be controlled by subsequent plastic processing;
[0022] (3) This W material with dispersed Y2O3 nanoparticles in the crystal and K bubbles at the grain boundaries is a special soft / hard phase composite strengthened W material, which combines the high temperature strengthening advantages of WK and the room temperature strengthening advantages of ODS-W, which is conducive to expanding the applicability of W materials in high temperature environments. This also provides a new way to develop high-strength W alloy materials with excellent high temperature performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope photograph of the cross section of the sintered body in Example 1, in which the black arrows indicate K bubbles.
[0024] Figure 2 This is a transmission electron microscope bright field morphology image of the sintered body sample in Example 1, in which the white arrows schematically show the positions of the dispersed spherical Y2O3 oxide nanoparticles. DETAILED DESCRIPTION
[0025] The specific preparation process and effects of the present invention are further described below through three specific examples.
[0026] Example 1 W-K-0.3wt.%Y sintered body
[0027] (1) The first step is to prepare Al 45 Y 55 Powder material
[0028] First, industrial pure metal is used as raw material, and the atomic percentage composition is Al 45 Y 55 The alloy was placed in a water-cooled copper crucible in a non-consumable arc melting furnace and evacuated to 3×10 -2 Pa, and filled with 0.02MPa of industrial pure Ar gas for non-consumable arc melting, the working current of melting is 150A; the alloy is turned upside down and repeatedly melted 3 times to obtain Al with uniform composition 45 Y 55 Alloy ingot, the weight loss of the alloy before and after smelting is less than one thousandth.
[0029] Al 45 Y 55 The alloy ingot is crushed and placed in a graphite crucible for atomization and powder making: it is heated to 1100℃ (slightly higher than Al 45 Y 55 The powder was cooled by spraying (the spray pressure of the atomizing gas was 5 MPa and the aperture of the nozzle of the guide rod was 1 mm) to obtain a spherical powder with a particle size of 5 to 20 μm. The X-ray diffraction spectrum of the powder showed the typical diffuse package characteristics of the amorphous structure, and there was no sharp crystal diffraction peak, confirming that the powder was an amorphous structure.
[0030] (2) The second step is to prepare Al 45 Y 55 +AKS-W composite powder
[0031] AKS-W powder (commercially available, 3.1 μm, K: 30 ppm, Al: 35 ppm, O: 0.10 wt.%) and Al 45 Y 55 Amorphous powder (screened with 1000 mesh and 2000 mesh) is used as raw material, and the composition is weighed and configured as AKS-W + 0.6wt.%Al 45 Y 55The composite powder (corresponding to the nominal composition of WK-0.3wt.%Y target alloy) was prepared. The powders were mixed and loaded into a ball mill together with grinding balls (material-to-ball ratio of 1:5) and subjected to high-energy ball milling in anhydrous ethanol medium environment. The ball mill speed was 150rpm and the ball milling time was 10h. The ball milled powder was taken out and dried in a vacuum drying oven for use.
[0032] (3) The third step is to prepare a WK-0.3wt.%Y sintered body by vacuum hot pressing
[0033] Pour about 100 g of the composite powder obtained in step 2 into a graphite mold, place it in a vacuum hot pressing sintering furnace, and evacuate to 1×10 -2 Pa, and preloaded with 30MPa; then heated to 1200℃ at a heating rate of 100℃ / min and kept warm for 60min, the first stage of sintering treatment, at this time Al 45 Y 55 Amorphous melting, taking advantage of liquid phase sintering, fully dissolve Y into W grains, and combine with O in them to form Y oxide; then continue to heat up to 1850℃ at a rate of 100℃ / min and keep warm for 90min to implement the second stage of sintering. In this stage, the compounds in AKS-W powder are mainly decomposed, and elements such as Al and Si are fully volatilized to form K bubbles. At the same time, Y and O are further fully combined to form oxides. The sintering pressure of the two stages is 70MPa. After sintering, the sample is cooled to room temperature with the furnace, taken out, and density and microstructure morphology are observed.
[0034] The density of the sintered sample was measured by the drainage method and was about 99.0%. Figure 1 The scanning electron microscope (SEM) morphology of the cross section of the sintered body is given, from which it can be seen that the average size of the matrix W grains is about 4μm, and the black arrow schematically points out the location of the K bubble, and the size of the K bubble is between 100 and 500nm; further transmission electron microscope (TEM, with energy spectrum accessory) analysis shows that the matrix of the sintered body is W polycrystal, and spherical nanoparticles are generated inside the grains and on the grain boundaries. The atomic percentage composition of the nanoparticles measured by the energy spectrum is close to Y2O3. The size of the oxide particles is between 20-50nm, and the volume fraction is about 0.5%. It is evenly and dispersedly distributed on the matrix material, as shown in the attached Figure 2 As shown; at the same time, 150nm K bubbles were also found at the grain boundaries.
[0035] Example 2 W-K-3wt.%Y sintered body
[0036] (1) The first step is to prepare Al 25 Y 75 Powder material
[0037] First, industrial pure metal is used as raw material, and the atomic percentage composition is Al 25 Y 75 The alloy was placed in a water-cooled copper crucible in a non-consumable arc melting furnace and evacuated to 1×10 -2 Pa, and filled with 0.01MPa of industrial pure Ar gas for non-consumable arc melting, the working current of melting is 120A; the alloy is turned upside down and repeatedly melted 3 times to obtain Al with uniform composition 25 Y 75 Alloy ingot, the weight loss of the alloy before and after smelting is less than one thousandth.
[0038] Al 25 Y 75 The alloy ingot is crushed and placed in a graphite crucible for atomization and powder making: it is heated to 1000℃ (slightly higher than Al 25 Y 75 The mixture was cooled by spraying (the spray pressure of the spray gas was 2 MPa and the aperture of the nozzle of the guide rod was 1 mm) to obtain spherical powder with a particle size of 10 to 30 μm. The X-ray diffraction spectrum of the powder has the diffuse package characteristics of a typical amorphous structure.
[0039] (2) The second step is to prepare Al 25 Y 75 +AKS-W composite powder
[0040] AKS-W powder (commercially available, 9.0 μm, K: 90 ppm, Al: 55 ppm, O: 0.15 wt.%) and Al 25 Y 75 Amorphous powder (screened with 600 mesh and 800 mesh) is used as raw material, weighed and configured with the composition of AKS-W + 4wt.%Al 25 Y 75 The composite powder (corresponding to the nominal composition of the target alloy WK-3wt.%Y) was prepared. The powders were mixed and loaded into a ball mill together with grinding balls (material-ball ratio of 1:10), and high-energy ball milling was performed in anhydrous ethanol medium environment. The ball mill speed was 200rpm and the ball milling time was 30h. The ball milled powder was taken out and dried in a vacuum drying oven for use.
[0041] (3) The third step is to prepare a WK-3wt.%Y sintered body by vacuum hot pressing
[0042] Pour about 100 g of the composite powder obtained in step 2 into a graphite mold, place it in a vacuum hot pressing sintering furnace, and evacuate to 1×10 -2 Pa, and preloaded with 30MPa; then heated to 1100℃ at a heating rate of 100℃ / min and kept warm for 60min, Al25 Y 75 The amorphous material melts, dissolving Y fully into the W grains and combining with O in them to form oxides; then the temperature is raised to 1700℃ and kept for 120min to decompose the compounds in the AKS-W powder to form K bubbles. The sintering pressure of the two stages is 70MPa. After sintering, the sample is cooled to room temperature with the furnace and taken out.
[0043] The density of the sintered body measured by the drainage method is 97%; the results of scanning electron microscopy and transmission electron microscopy observations show that the matrix of the sintered body is polycrystalline W, and its grain size is about 10μm, and K bubbles and Y2O3 nanoparticles are evenly distributed on the matrix, and the size of K bubbles is between 500nm and 1μm; the nanoparticles are spherical, with a size of 30 to 50nm, and the volume fraction is about 5%.
[0044] Example 3 W-K-2wt.%Y sintered body
[0045] (1) The first step is to prepare Al 35 Y 65 Powder material
[0046] First, industrial pure metal is used as raw material, and the atomic percentage composition is Al 35 Y 65 The alloy was placed in a water-cooled copper crucible in a non-consumable arc melting furnace and evacuated to 2×10 -2 Pa, and filled with 0.015MPa of industrial pure Ar gas for non-consumable arc melting, the working current of melting is 135A; the alloy is turned upside down and repeatedly melted 3 times to obtain Al with uniform composition 35 Y 65 Alloy ingot, the weight loss of the alloy before and after smelting is less than one thousandth.
[0047] Al 25 Y 75 The alloy ingot is crushed and placed in a graphite crucible for atomization and powder making: it is heated to 1050℃ (slightly higher than Al 35 Y 65 The mixture was cooled by spraying (the spray pressure of the atomizing gas was 4 MPa and the aperture of the nozzle of the guide rod was 1 mm) to obtain spherical powder with a particle size of 6 to 23 μm. The X-ray diffraction spectrum of the powder has the typical diffuse package characteristics of an amorphous structure, confirming that it is an amorphous structure.
[0048] (2) The second step is to prepare Al 35 Y 65 +AKS-W composite powder
[0049] AKS-W powder (commercially available, 1.3 μm, K: 30 ppm, Al: 25 ppm, O: 0.10 wt.%) and Al 35 Y 65 Amorphous powder (screened with 1340 mesh and 2000 mesh) was used as raw material, and the composition was weighed and configured as AKS-W + 3.1wt.%Al 35 Y 65 The composite powder (corresponding to the nominal composition of WK-2wt.%Y target alloy) was prepared. The powders were mixed and loaded into a ball mill together with grinding balls (material-ball ratio of 1:8), and high-energy ball milling was performed in anhydrous ethanol medium environment. The ball mill speed was 180rpm and the ball milling time was 20h. The ball milled powder was taken out and dried in a vacuum drying oven for use.
[0050] (3) The third step is to prepare a WK-2wt.%Y sintered body by vacuum hot pressing
[0051] Pour about 100 g of the composite powder obtained in step 2 into a graphite mold, place it in a vacuum hot pressing sintering furnace, and evacuate to 1×10 -2 Pa, and preloaded with 30MPa; then heated to 1150℃ at a heating rate of 100℃ / min and kept warm for 60min, Al 35 Y 65 The amorphous material melts, and Y is fully dissolved into the W grains, combining with O in them to form oxides; then the temperature is raised to 1800℃ and kept for 60 minutes, so that the compounds in the AKS-W powder decompose to form K bubbles, and Y and O fully react to form oxides. The sintering pressure of the two stages is 70MPa. After sintering, the sample is cooled to room temperature with the furnace and taken out.
[0052] The density of the sintered body measured by the drainage method is 98.2%; the results of scanning electron microscopy and transmission electron microscopy observations show that the matrix of the sintered body is polycrystalline W, and its grain size is about 2μm, and K bubbles and Y2O3 nanoparticles are evenly distributed on the matrix, and the size of K bubbles is between 100 and 350nm; the nanoparticles are spherical, with a size of 5 to 25nm, and the volume fraction is about 3.2%.
[0053] The above results show that: this embodiment finally prepares a WK-Y2O3 sintered body through vacuum hot pressing sintering technology in a hydrogen-free environment, that is, nano-scale Y2O3 particles are uniformly and dispersedly distributed on the WK matrix, which can achieve the composite strengthening of hard oxide particles and soft K bubbles on W crystal materials.
[0054] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A W-based material reinforced by K-bubble and nano-oxide composite, characterized in that: The structural characteristics of the W-based material are: a W polycrystal with a size of 2 to 10 μm is used as the matrix; the nominal content of K in the material is 30 to 90 ppm, and it appears at the grain boundary in the form of K bubbles, and the final size and distribution state of the K bubbles are regulated by subsequent plastic processing; Y2O3 nanoparticles are dispersed and evenly distributed on the W matrix, and the size and number density of the Y2O3 nanoparticles are regulated by the sintering process, and the volume fraction corresponding to the number density is between 0.5% and 5%, and the volume fraction is regulated by the sintering raw material ratio and the sintering process; The size of the K bubble is 0.1-1 μm; the size of the Y2O3 nanoparticle is 5-50 nm.
2. A method for preparing the W-based material compositely reinforced with K bubbles and nano-oxides according to claim 1, characterized in that: First, Al with a melting point below 1100°C was prepared by arc melting combined with melt atomization technology. 100-a Y a Amorphous powder, wherein 55≤a≤75, atomic percentage; secondly, sieving it and combining it with commercially available AKS-W powder as raw materials, mixing the ingredients based on the nominal composition of the target W alloy sintered body, mixing and placing in anhydrous ethanol medium environment for high-energy ball milling, and obtaining Al 100-a Y a +AKS-W composite powder, drying; finally, a W material with dispersed Y2O3 nanoparticles on the matrix and K bubbles formed at the grain boundaries is prepared by a hot pressing sintering method.
3. The method for preparing a W-based material compositely reinforced with K bubbles and nano-oxides according to claim 2, characterized in that: The preparation of Al 100-a Y a The steps for amorphous powder materials are: Industrial pure metal is used as raw material, and the atomic percentage composition is Al 100-a Y a The alloy was placed in a water-cooled copper crucible in a non-consumable arc melting furnace and vacuumed to ≤3×10 -2 Pa, and fill with 0.01-0.02MPa industrial pure Ar gas for non-consumable arc melting, the working current of melting is 120-150A; turn the alloy upside down and melt repeatedly for many times to obtain Al with uniform composition 100-a Y a Alloy ingots; Al 100-a Y a The alloy ingot is crushed and placed in a graphite crucible for atomization and powder making: medium frequency induction heating is used to heat the alloy to a temperature higher than Al 100-a Y a The alloy is kept warm at its melting point for 2 to 5 minutes; it is sprayed out and cooled using atomization technology to obtain a spherical powder material with a particle size of 5 to 30 μm, which is then sieved and set aside.
4. The method for preparing a W-based material compositely reinforced with K bubbles and nano-oxides according to claim 2, characterized in that: The preparation of Al 100-a Y a +AKS-W composite powder steps are: Commercially available AKS-W powder was used as the matrix material, and Al 100-a Y a Amorphous powder is used as an additive, weighed, configured, and composite powder. The general formula of the composite powder is AKS-W+0.6~4.0wt.%Al 100-a Y a , and the corresponding nominal composition of the target alloy is WK-0.3~3.0wt.%Y, wherein Y mainly exists together with O in the form of Y2O3; after mixing, it is loaded into a ball mill together with grinding balls, and high-energy ball milling is performed in anhydrous ethanol medium environment, the ball mill speed is 150~200rpm, and the ball milling time is 10~30h; finally, the ball-milled powder is taken out, dried in a vacuum drying oven and set aside.
5. The method for preparing a W-based material compositely reinforced with K-bubbles and nano-oxides according to claim 4, characterized in that: In the high-energy ball milling process, the material-to-ball ratio is 1:5 to 1:
10.
6. The method for preparing a W-based material compositely reinforced with K bubbles and nano-oxides according to claim 2, characterized in that: The WK-Y2O3 sintered body is prepared by vacuum hot pressing sintering, and the steps are as follows: Al 100-a Y a +AKS-W composite powder was placed in a vacuum hot pressing sintering furnace for sintering to obtain the target alloy sintered body; the sintering preload pressure was 30MPa and the vacuum degree was 1×10 -2 Pa, mainly includes two stages: the sintering temperature of the first stage is 1100-1200℃, the sintering pressure is 70MPa, and the insulation time is 60min; the sintering temperature of the second stage is 1700-1850℃, the sintering pressure is 70MPa, and the insulation time is 60-120min; then the furnace is cooled to room temperature to obtain the product.
Citation Information
Patent Citations
Method for preparing nano oxide dispersion reinforced superfine crystal tungsten-based composite material
CN101880808A
Method for preparing rare-earth oxide dispersion strengthened fine-grained tungsten material
CN105518169A